Platelet-rich plasma in the pathologic processes of tendinopathy: a review of basic science studies - Lu, Jialin; Li, Han; Zhang, Ziyu; Xu, Rui; Wang, Jincheng; Jin, Hui (Frontiers in Bioengineering and Biotechnology, 2023)
Tendinopathy is a medical condition including a spectrum of inflammatory and degenerative tendon changes caused by traumatic or overuse injuries. The pathological mechanism of tendinopathy has not been well defined, and there is no ideal treatment currently available. Platelet-rich plasma (PRP) is an autologous whole blood derivative containing a variety of cytokines and other protein components.Various basic studies have found that PRP has the therapeutic potential to promote cell proliferation and differentiation, regulate angiogenesis, increase extracellular matrix synthesis and modulate inflammation in degenerative tendons. Therefore, PRP has been widely used as a promising therapeutic agent for tendinopathy. However, controversies exist regarding the optimal treatment regimen and efficacy of PRP for tendinopathy. To better understand how PRP effects on tendinopathy and to explore the reason for the differences in clinical trial outcomes, the focus of this review is on the specific molecular and cellular mechanisms by which PRP manipulates tendon healing. This article has pointed out the future direction of basic research and clinical application of PRP in the treatment of tendinopathy as well, which will play a guiding role in the design of PRP treatment protocols for tendinopathy.